STRATEGIC ROLE OF CONSUMER ETHNOCENTRISM, SOCIAL MEDIA MARKETING, AND BRAND AMBASSADORSHIP IN SHAPING PURCHASE DECISIONS FOR LOCAL INDONESIAN SKINCARE BRANDS ON E-COMMERCE PLATFORMS - Yang, Elaine; Kembau, Agung Stefanus; Tarigan , Arihta; Lendo, Fresi Breatrix (FEB Universitas Sam Ratulangi Manado, 2024)
The rapid advancement of technology in Indonesia has significantly impacted various economic sectors, with the beauty industry, particularly skincare, experiencing remarkable growth. This research investigates the factors influencing purchase intention and purchase decision for local skincare brands, exemplified by brands such as Somethinc, Scarlett Whitening, and Ms. Glow. Employing a quantitative approach, the study explores the relationships between key variables. Primary data was gathered through an online questionnaire from 140 qualified respondents out of an initial 142. Secondary data was sourced from existing journals, articles, and books. The data was analyzed using SmartPLS version 3.0 with a purposive sampling technique, determined by the Cochran formula. The findings reveal that Social Media Marketing, Brand Ambassadors, and Consumer Ethnocentrism significantly and positively affect both purchase intention and purchase decision. Furthermore, purchase intention itself positively and significantly influences purchase decision. The study also demonstrates that purchase intention can partially mediate the relationship between Social Media Marketing and Consumer Ethnocentrism on purchase decision, but does not mediate the relationship between Brand Ambassadors and purchase decision through purchase intention. These insights offer valuable implications for the strategic marketing of local skincare brands in Indonesia. Keywords: Skincare, Local Brand, Social Media Marketing, Brand Ambassador, Consumer Ethnocentrism, Purchase Intention, Purchase Decision, Somethinc, Scarlett Whitening, Ms.Glow.